Sunitinib rechallenge with dose escalation in progressive metastatic renal cell carcinoma: A case report and literature review. Issue 31 (August 2018) - Zhang, Xingming; Shen, Pengfei; Yao, Jin; Chen, Ni; Liu, Jiyan; Zeng, Hao
Abstract: Rationale: We aimed to present a case of sunitinib rechallenge with dosage escalation after disease progression, hopefully, providing an optional approach to the personalized medication management of progressive metastatic renal cell carcinoma (mRCC). Patient concerns: The patient was admitted to hospital due to right kidney mass, with merged enlargement of retroperitoneal lymph nodes. Subsequent surgery and sunitinib treatment was administered. Diagnoses: Postoperative pathologic diagnosis was type II papillary renal cell carcinoma (pRCC) (Fuhrman grade 3) with metastases of retroperitoneal lymph nodes (T1aN1M0). Interventions: The patient underwent cytoreductive nephrectomy followed by treatment of sunitinib standard therapy (4/2 schedule) and alternative schedules according to different disease status. The patient received alternative 2/1 schedule while experiencing grade 3/4 adverse events. Re-challenge with sunitinib upon disease progression and metastasectomy were given. After second disease progression, sunitinib rechallenge with dose escalation was administered. Around 2/1 schedule showed desirable efficacy and better tolerance. Outcomes: After 4 months of sunitinib individualized treatment, a complete response with retroperitoneal metastases was achieved. Rechallenge with sunitinib after disease progression and also rechallenge with dose escalation after second disease progression were effective. Lessons: Cessation of sunitinib in patients with complete response is not suggested. Also, strategy of subsequently administered sunitinib after metastasectomy is seemed to be effective. What is more, sunitinib rechallenge with escalation to 62.5 mg probably possess value in progressive mRCC and has a well tolerance when sunitinib is rechallenged. Based on this case, we probe a feasible alternative strategy in personalized therapy of sunitinib, hoping for providing referable insights into the detailed strategies of individual treatment for patients with mRCC.